Manajemen Kurikulum Muatan Lokal Berbasis Keterampilan Kerja di MA Al – Ihsan Kalikejambon Tembelang Jombang - Anwar, Choirul; Sembodo, Sigit Priyo (Menara Tebuireng, 2025)
Local content in an education unit is a set of plans and arrangements regarding the objectives, content and learning materials prepared by the education unit by considering the surrounding potential so that the vision and mission of the education unit can be achieved. So in this case, an education unit is required to plan, organize, carry out matters related to local content and evaluate so that the achievement of learning can be maximized. Through the learning of local content of work skills, it is expected that students not only gain global academic knowledge, but also have concern for the social and cultural values that exist around them. In addition, the purpose of this learning is to equip the generation with life skills, so that students can adapt to society and compete in the world of work.   This research uses a descriptive qualitative approach, which aims to describe, explain, and reveal the results regarding the management of new student admissions. The data collection techniques include interviews, observation, and documentation. The techniques used are 1) observation 2) triangulation and 3) data checking. The results of research by researchers related to the application of work skills-based local content curriculum at MA Al - Ihsan Kalikejambon Tembelang Jombang are: 1) Planning local content curriculum work skills in accordance with the vision, mission, and objectives of the madrasah. 2) Curriculum organization which begins with curriculum mapping, schedule preparation based on the academic calendar, division of teaching duties, and arrangement of teaching hours through the selection process. 3) Implementation of the curriculum for the work skills program at MA Al-Ihsan emphasizes more on direct practical activities after the delivery of material. 4) Curriculum evaluation activities include evaluation of students and educators.